Методи регулювання трудових конфліктів у робочих групах іт-компаній - Федоренко, Є. Д. (ХНУРЕ, 2019)
Nowadays, the influence of Ukraine in the field of information technology has increased. Mostly medium and small IT companies are created.And of course, interpersonal relations, professional, business relations should be built there. Therefore, the study of methods for resolving conflicts that takes into account the specifics of the functioning of such groups is actualized. The object of this study is the specificity of conflicts that arise in the working groups (labor collectives) of IT companies, the subject - methods for resolving such conflicts. In this article, we investigate one of the methods of conflict management in the labor collective of IT company. We are going to speak about method that we found the most appropriate, according to specific of Ukrainian companies.